Chemical characteristics of fish sticks from different parts of catfish (Clarias sp.): Karakteristik kimia stik ikan dari bagian ikan lele (Clarias sp.) yang berbeda - Kusumaningrum, Indrati; Sulistyawati, Septiana (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Catfish is a widely cultivated freshwater fish because of its quick and easy farming and stable market price. Catfish is consumed by frying, grilling, or processing into meatballs, nuggets, shredded meat, and fish sticks. This study aimed to assess the best treatment for different parts of catfish used to make fish sticks based on their calcium and phosphorus content. A Completely Randomized Design (CRD) was employed with three treatments: minced catfish (MC), HFC (head and fishbone catfish (HFC), and WGGC (whole gilled and gutted catfish (WGGC). The parameters analyzed included proximate, calcium, and phosphorus content. The tests showed significantly different results (p<0.05) in terms of moisture, ash, fat, carbohydrate, calcium, and phosphorus content of the three treatments. Meanwhile, the protein content of fish sticks in this study was not significantly different, namely 10.67-10.92%. Fish sticks made from gilled and gutted whole fish (meat and bones) had a calcium content of 0.68±0.02% and a phosphorus content of 0.083±0.00%, thus having the potential to be an alternative processed product with minimal waste (zero-waste).